Worldsheet kinematics, dressing factors and odd crossing in mixed-flux AdS3 backgrounds - Olof Ohlsson Sax; Dmitrii Riabchenko; Bogdan Stefański jr. (Journal of High Energy Physics)
Abstract String theory on AdS3 × S3 × T4 geometries supported by a combination of NS-NS and R-R charges is believed to be integrable. We elucidate the kinematics and analytic structure of worldsheet excitations in mixed charge and pure NS-NS backgrounds, when expressed in momentum, Zhukovsky variables and the rapidity u which appears in the quantum spectral curve. We discuss the relations between fundamental and bound state excitations and the role of fusion in constraining and determining the S matrices of these theories. We propose a scalar dressing factor consistent with a novel u-plane periodicity and comment on its close relation to the XXZ model at roots of unity. We solve the odd part of crossing and show that our solution is consistent with fusion and reduces in the relativistic limit to dressing phases previously found in the literature.